The Concept of Religious Moderation: A Study of Maudhu’i’s Interpretation - Rifki Azkya Ramadhan; Nurul Fadhilah Ramadhani Arqam; Asep Abdul Muhyi (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
This study aims to explore the concept of religious moderation from the perspective of Islam through a descriptive analysis approach. In this context, religious moderation is interpreted as a balanced attitude that encompasses various aspects of religious life. The results of the descriptive analysis of the Qur'an and relevant Islamic literature identify that religious moderation in Islam embodies values such as simplicity, tolerance, and justice. The Islamic perspective on religious moderation is reflected in the teachings of the Qur'an and Sunnah, emphasizing the importance of avoiding extremism and fanaticism in religious practice. In the Qur'an, religious moderation is represented by the phrase